A direct-conversion receiver for the 3G WCDMA standard. - Gharpurey, R.
A highly integrated direct-conversion receiver that satisfies requirements of the third-generation wide-band code-division multiple-access mobile phone standard is described. The receiver integrated circuit includes the front-end low-noise amplifier, downconversion mixers, baseband variable-gain amplifiers, channel-select filters, and the frequency synthesizer. External components are limited to matching elements required for the low-noise amplifier and the mixers and two passive band-select filters. The receiver is implemented in a SiGe BiCMOS process and consumes a total current of 46 mA from a 2.7-V supply.
Keywords: 2.7 V; 3G WCDMA standard; 46 mA; BiCMOS; SiGe; Baseband variable-gain amplifiers; Channel-select filters; Direct-conversion receiver; Downconversion mixers; Frequency synthesizer; Front-end low-noise amplifier; Low-noise amplifier; Matching elements; Mobile phone standard; Passive band-select filters; Wide-band code-division multiple-access.